(untitled) - Bentley, Jerry H. (New York, N.Y., 2011)
Connect students to the stories of history. Connect students to the experience of history. Connect students to success in history. At McGraw-Hill, we have dedicated the past few years to deepening our understanding of student and instructor experience.
Keywords: World history,Lịch sử thế giới